Pengenalan Teknologi Komputer Kepada Siswa Sekolah Dasar MI Darul Hasan Tangerang-Banten - Hendra Jatnika; M. Farid Rifai; Yessy Fitriani; Marsela Tri Anggrainie; Muhammad Zaid Al Khair; Muh.Narya Nash; Tyara Anastasya; Joey Andrew Fransisco Sihombing; Azizah Arip Rambe; Grace Augustin Sinaga; Yusleli Siagian; Arfani Lovina Br Stendel; Azmi Azis; Rizka Putri Aulia Rusdi; Adinda Musika Permata; Mohamad Tanwirul Akbar; Alexandro Nesta; Ruth Syalomitha hutabarat (Politeknik Piksi Ganesha Indonesia, 2024)
MI Darul Hasan Elementary School (SD) Tangerang, Banten is one of the educational units at MI level in Cipondoh Makmur, Kec. Cipondoh, Tangerang City, Banten. Introducing computer technology to students is crucial in facing the increasingly developing digital era. Community service in the form of introducing computer technology to students is an effort to improve and introduce computer components among children. Community service is carried out at SD MI Darul Hasan Tangerang-Banten with the aim of providing students with an understanding of computer technology, especially computer components, by providing training and forcing students. With this service, it is hoped that students' understanding of basic computer concepts and knowledge of technology in everyday learning will increase. With this activity, it is hoped that students will be better prepared to face technological developments in the future. The success of this service can also be used as a model for similar activities in other educational institutions to support the development of digital knowledge among children